CORRELATION AMONG DYSLEXIA, DYSPRAXIA AND DYSCALCULIA IN STUDENTS WITH LEARNING DYSABILITIES - Tūbele, Sarmīte (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The article is devoted to evaluate the correlation among dyslexia, dyspraxia and dyscalculia in students with learning dysabilities. There is a point of view that students with learning dysabilities mostly have dyspraxia, but not all of them have dyscalculia or dyslexia. There is a necessity to have theoretical findings and state criteria for evaluation to carry out empirical research. Students with learning dysabilities have difficulties in many areas, but it is not possible to assure that all of them meet the same problems.